Quality of ‘Baigent’ apples as a function of pre-harvest application of aminoethoxyvinylglycine and ethephon stored in controlled atmosphere - Soethe C.* (2022)
© 2022– The objective of this work was to evaluate the effects of pre-harvest application on ‘Baigent’ apple trees cultivated under black anti-hail nets with aminoethoxyvinylglycine (AVG), in a single or split dose, combined or not with ethephon, on the quality, the antioxidant activity, and the content of phenolic compounds of the fruits after storage in controlled atmosphere (CA). The pre-harvest applications of AVG alone, both at a dose of 0.125 g L−1, as well as in split dose and at a dose of 0.0625 g L−1, reduced the rate of ethylene production, showed less yellowing fruits and a lower incidence of cracks, maintaining high flesh firmness, texture attributes, and fruit acidity, without causing negative effects on the incidence of mealiness and decay. The pre-harvest applications of AVG at a dose of 0.125 g L−1 and in split dose combined with ethephon also contributed to the reduction of the ethylene production rate and yellowing, showed high flesh firmness and texture, however, it showed a high incidence of decay and cracking when ethephon was combined with AVG at a dose of 0.125 g L−1. In the skin, application of AVG only at a dose of 0.125 g L−1 reduced the total phenolic compounds values, however, total antioxidant activity was reduced with any form of AVG application. In the flesh, there was no effect of pre-harvest application of AVG. Regardless of the dose and form of application, AVG reduced the contents of chlorogenic acid, phloridizin, and epicatechin in the skin of fruits harvested at commercial harvest.